Piling Work Police District Headquarters, Pasir Mas, Kelantan / Muhammad Azri Che Wil - Muhammad Azri, Che Wil (2017)
Public Work Department (PWD) was established in 1872 and headed by Major J.F.A McNair. The events that lead to the establishment of the PWD began in early 1872 when the British East India Company - trade between England, India, and China - need a secure station to improve their trading ships. They discover Penang suitable for this purpose due to its strategic location.